Odpowiedzi

2009-12-15T13:11:22+01:00
X=1-y+z
-2(1-y+z)=0
1-y+z - 3y +z =-3

-2+2y-2z=0 |:2
4-4y-2z=0 |:2

-1+y-z = 0
2-2y-z = 0

z = y-1
2-2y-y-1=0

1-3y=0

y=1/3

z=1/3 - 1 =-2/3

x=1- 1/3 - 2/3 =0
2009-12-15T13:15:55+01:00
X+y+z=1
-2x+y+z=0
x-3y+z=-3

x=1-y-z
-2(1-y-z)+y+z=0
1-y-z+3y+z=-3

x=1-y-z
-2+2y+2z=0
1-+2y=-3

x=1-y-z
-2+2y+2z=0
2y=-2

x=1-y-z
-2+2y+2z=0
2y=-2/2

x=1-y-z
-2+2y+2z=0
y=-1

x=1-(-1)-z
-2+2*(-1)+2z=0
y=-1

x=2-z
-4+2z=0
y=-1

x=2-z
2z=4
y=-1

x=2-z
2z=4/2
y=-1

x=2-z
z=2
y=-1

x=2-2
z=2
y=-1

x=o
z=2
y=-1